38 DIFFERENCE IN THE FREQUENCY OF THE C3435T SINGLE NUCLEOTIDE POLYMORPHISM IN THE MDR1 GENE DOES NOT EXPLAIN THE HIGHER RATE OF NEW ONSET DIABETES AFTER TRANSPLANTATION IN BLACKS. (1st March 2005) - Tedla, F.; Stratilatova, M.; Solomon, W.; Salifu, M.; Distant, D.; Markell, M.
Abstract : NODAT is more frequently observed in black patients than Caucasians. C3435T polymorphisms have been postulated to affect serum levels of tacrolimus, an immunosuppressant associated with development of diabetes. We tested if C3435T polymorphisms were associated with risk of NODAT in various races. Methods: Patients were considered to have NODAT if they were diagnosed to have diabetes after initiation of tacrolimus and had two fasting blood glucose measurements in the normal range in the last 18 months prior to transplantation. Controls had normal glucose after at least one year of treatment with tacrolimus. Polymorphism at position 3435 in the MDR1 gene was determined with amplification of genomic DNA by polymerase chain reaction and digestion of the product with Sau3AI followed by agorose gel electrophoresis to separate the fragments. Results: Sixteen patients who met the criteria for NODAT were compared to 17 controls. Seven patients could not be conclusively classified into either category. Twenty-six were blacks (15 Caribbeans, 9 African-American 2 Hispanic), and 14 were non-blacks (6 Caucasians, 5 Hispanic, 2 Indians, 1 Yemeni). We found that there was a significant difference in the frequency of the CC, CT, TT polymorphisms between blacks and non-blacks (46.2%, 50%, 3.8% vs. 7.1%, 64.3%, 28.6%, χ2 = 9.05, p = 0.01). Comparing patients with NODAT and controls, there was no significant difference in the distribution of the different single nucleotide polymorphisms (SNPs), gender distribution, positive family history of diabetes (50% vs. 50%), number of blacks vs. non-blacks (52.6% vs. 47.4%), mean age (50.2 ± 2.9 vs. 43.2 ± 3.6), mean body mass index (28 ± 1.2 vs. 31 ± 1.4) or dose-weight-adjusted trough serum tacrolimus levels (81 ± 15.3 vs. 102 ± 21 ng/mL). The different SNPs were in Hardy-Weinberg equilibrium using the χ2 goodness-of-fit test. Conclusion: There is a significant difference in the distribution of the C3435T polymorphism of the MDR1 gene between blacks and non-blacks that is not associated with difference in trough tacrolimus levels or risk for NODAT. Larger studies are needed to validate these observations.